If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4 + -2x) + (2x + -1) = 9 (4 * -2 + -2x * -2) + (2x + -1) = 9 (-8 + 4x) + (2x + -1) = 9 Reorder the terms: -8 + 4x + (-1 + 2x) = 9 Remove parenthesis around (-1 + 2x) -8 + 4x + -1 + 2x = 9 Reorder the terms: -8 + -1 + 4x + 2x = 9 Combine like terms: -8 + -1 = -9 -9 + 4x + 2x = 9 Combine like terms: 4x + 2x = 6x -9 + 6x = 9 Solving -9 + 6x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 6x = 9 + 9 Combine like terms: -9 + 9 = 0 0 + 6x = 9 + 9 6x = 9 + 9 Combine like terms: 9 + 9 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| F(5)=292-17x | | 3hx+4hx+6hx=1 | | 10x-6=8x+11 | | 4x-4+2x+16=180 | | 5(2+y)=8 | | 13(x+13)=5x+113 | | 198=127-v | | 12y-1/5=7 | | M^2+8m-18=0 | | -18=3v+3 | | lg(3x+1)=4 | | (x-2)(1x-8)=0 | | 4y-2=-26 | | -5(-4x-10)=150 | | 2x+50+70-10x+x*2+40=180 | | -4-7x=11+8x | | 5x+10y=120 | | 5-20a^6=0 | | (2t^5/3s^4)^2 | | 1/8x-7 | | -13=3b-2(b+5) | | 8x^2+80x=-16 | | 25x^4-64x^6=0 | | -12=8x+8-3x | | 3q-(q-5)=-13 | | -3n+5n=16 | | 8x+17x-10=5(5x+6) | | -18=4v+5v | | (y^2+2y-1)+(y^2-2y-1)= | | 3x^2+20x-23=0 | | 10p-4=4p-10 | | 3y-5(y-2)=36 |